EFEKTIVITAS PENEGAKAN HUKUM TERHADAP TINDAKAN MENJUAL BUKU BAJAKAN MELALUI E-MARKETPLACE - Ni Nyoman Muryatini; I Gusti Bagus Agung Kusuma Atmaja (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Nowadays, activities of offering, selling, purchasing goods and services have changed along with the rapid development of information technology. These also encourage the changes in people’s behavior and lifestyle. Buying and selling goods and services were previously carried out through conventional markets, but now can be done through online markets, namely through e-marketplaces. Pirated books were widely sold at roadside stalls, but now they are sold through online sites, namely e-marketplaces. Based on the research conducted by the Indonesian Publishers Association (IKAPI), 54.2% of publishers found that pirated books of their work were sold through online markets during the pandemic of COVID-19. The problem studied in this study is the effectiveness of law enforcement against the sale of pirated books through e-marketplace. The research method used in this research is empirical juridical. Empirical juridical research refers to the research that analyzes and examines the workings of law in society. The results of the study indicate that the Copyright Act uses complaint offenses. The law enforcement officers cannot act proactively against copyright infringement. It often happens that the copyright holder does not know his copyrighted work has been pirated. The effectiveness of law enforcement against the sale of pirated books through e-marketplaces in Indonesia is currently not effective. This is shown by the number of cases of selling pirated books on e-marketplaces at this time.